2021
DOI: 10.3390/life11121375
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biomarkers in the Diagnosis and Treatment of Inflammatory Bowel Disease

Abstract: The number of patients with inflammatory bowel disease (IBD) is increasing worldwide. Endoscopy is the gold standard to assess the condition of IBD. The problem with this procedure is that the burden and cost on the patient are high. Therefore, the identification of a reliable biomarker to replace endoscopy is desired. Biomarkers are used in various situations such as diagnosis of IBD, evaluation of disease activity, prediction of therapeutic effect, and prediction of relapse. C-reactive protein and fecal calp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 166 publications
(191 reference statements)
2
15
0
Order By: Relevance
“…Among other inflammatory markers, FCP has proven to be the best biomarker for monitoring mucosal response to IFX therapy [ 53 , 54 , 55 ]. In our study we found that, although patients had high levels of ATIs, FCP decreased over the course of infusions.…”
Section: Discussionmentioning
confidence: 99%
“…Among other inflammatory markers, FCP has proven to be the best biomarker for monitoring mucosal response to IFX therapy [ 53 , 54 , 55 ]. In our study we found that, although patients had high levels of ATIs, FCP decreased over the course of infusions.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal healing is an important therapeutic goal in the management of UC, and biomarkers for the evaluation of mucosal healing have been widely used in clinical practice [ 26 ]. Endoscopic severity has been reported to predict the prognosis of UC, and the achievement of mucosal healing has been recognized to be important [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Moreover, recurrent hospitalizations in patients with COVID‐19 and frailty in elderly or diabetic patients during COVID‐19 infection are suggested to be also related to increased inflammatory burden. 14 , 15 , 16 The biomarkers that involved in the immune‐inflammatory and coagulation pathways, such as CRP, NLR, D‐D, have been used to assess the disease severity and prognosis of multiple chronic, inflammatory or autoimmune diseases, such as irritable bowel disease, 17 diabetes mellitus, 18 and Hashimoto's disease. 19 Therefore, accurate monitoring of inflammatory factors plays an important role in the judgment of disease progression and the selection of treatment strategies for COVID‐19 patients.…”
Section: Introductionmentioning
confidence: 99%